Bone and cortical bone thickness of mandibular buccal shelf for mini-screw insertion in adults - Nucera, Riccardo; Lo Giudice, Antonino; Bellocchio, Angela Mirea; Spinuzza, Paola; Caprioglio, Alberto; Perillo, Letizia; Matarese, Giovanni; Cordasco, Giancarlo (The Angle orthodontist, 2017)
To analyze the buccal bone thickness, bone depth, and cortical bone depth of the mandibular buccal shelf (MBS) to determine the most suitable sites of the MBS for mini-screw insertion. The sample included cone-beam computed tomographic (CBCT) records of 30 adult subjects (mean age 30.9 ± 7.0 years) evaluated retrospectively. All CBCT examinations were performed with the i-CAT CBCT scanner. Each exam was converted into DICOM format and processed with OsiriX Medical Imaging software. Proper view sections of the MBS were obtained for quantitative and qualitative evaluation of bone characteristics. Mesial and distal second molar root scan sections showed enough buccal bone for mini-screw insertion. The evaluation of bone depth was performed at 4 and 6 mm buccally to the cementoenamel junction. The mesial root of the mandibular second molar at 4 and 6 mm showed average bone depths of 18.51 mm and 14.14 mm, respectively. The distal root of the mandibular second molar showed average bone depths of 19.91 mm and 16.5 mm, respectively. All sites showed cortical bone depth thickness greater than 2 mm. Specific sites of the MBS offer enough bone quantity and adequate bone quality for mini-screw insertion. The insertion site with the optimal anatomic characteristics is the buccal bone corresponding to the distal root of second molar, with screw insertion 4 mm buccal to the cementoenamel junction. Considering the cortical bone thickness of optimal insertion sites, pre-drilling is always recommended in order to avoid high insertion torque.